The Role of Non Governmental Organisations in Social Development: The Case of Lower Manya Krobo Municipality. - Tetteh, Salome Kadi (UniMAC-GIJ, 2021)
The study therefore focused on examining the role of NGOs in promoting social development in rural Ghana using Lower Manya Municipality as a case. The study relied on the mixed methods approach and involved a total of 115 respondents who were mainly community members and NGO staff. Questionnaire, interview schedule and focus group discussion guide were used for data collection. The study found that that NGOs in the municipality had provided interventions in mostly education, health and provision of water and a few employment creation, gender equality and agriculture. Community members were generally satisfied with interventions in education, health and water provision with specific interventions like building schools, health education and screening and provision of boreholes. The promotion of human rights and local governance were not really focused on by these NGOs. With regard to the involvement of community members in the stages of project implementation, the study showed that NGOs in the municipality were doing well in that. It was also realised that NGOs had challenges in getting funds for their interventions, limited capacity, their relationships with international NGOs and political interference. It was therefore recommended that NGOs should strengthen ties with International NGOs (INGOs) and government institutions and this will go a long way to solve most of their problems. They should also involve community members from the planning stages through implementation to monitoring and evaluation.
Thesis
Keywords: Non Governmental Organisations, Social Development, Lower Manya Krobo Municipality, Ghana